2016
DOI: 10.1002/brb3.469
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy improves aerobic capacity of inpatients with major depressive disorder

Abstract: BackgroundUnipolar depression is one of the most common diseases worldwide and is associated with a higher cardiovascular risk partly due to reduced aerobic capacity.ObjectivesTherefore, the aim of our study was to examine whether a structured aerobic training program can improve aerobic capacity in inpatients with MDD (major depressive disorder).MethodsOverall, 25 patients (13 women, 12 men) diagnosed with MDD were included in the study. Parameters of aerobic capacity, such as maximum performance, maximum oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similarly, Kerling et al . 21 reported that maximum oxygen consumption did not differ significantly between exercise (includes patients with depression) and control (includes healthy participants) groups, although exercise (within-group) resulted in significant improvements in V̇ O 2max . However, these results may be the result of low statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Kerling et al . 21 reported that maximum oxygen consumption did not differ significantly between exercise (includes patients with depression) and control (includes healthy participants) groups, although exercise (within-group) resulted in significant improvements in V̇ O 2max . However, these results may be the result of low statistical power.…”
Section: Discussionmentioning
confidence: 93%
“…This minimum recommended dose of exercise was prescribed to increase participant adoption and adherence since low-active people with depression generally lack motivation to begin an exercise program ( 84 ). Also, exercise prescriptions based on this intensity performed over 6 weeks have shown to significantly improve cardiorespiratory fitness and depression symptoms in patients with MDD ( 85 , 86 ). The research has also found that a combining aerobic with resistance training is more effective than aerobic exercise alone in improving depressive symptoms and cognitive function ( 87 , 88 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic MDD is common, with a lifetime prevalence of ~5% in the general population; around 20-30% of acutely depressed individuals typically go on to develop a chronic disease course (1,2). Chronic MDD is distinguished from acute MDD by an earlier onset (1), increased comorbidity with axis 1 disorders (1,3,4), higher rates of personality disorders (5), higher rates of childhood trauma (6), greater suicidality (7) and functional impairment (1,8), higher rates of mood disorders in relatives (9,10), and worse treatment outcome (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Key factors contributing include the increased rate of the metabolic syndrome in MDD (17), increased rates of type-2 diabetes mellitus (18,19), increased intra-abdominal adipose tissue (20), dysregulation of the hypothalamuspituitary-adrenal axis (HPAS) with subsequent alterations in cortisol concentrations (21), dysregulation of pro-and anti-inflammatory cytokines (22), and poor lifestyle habits (e.g. smoking, physical activity, dietary factors) (2,23,24).…”
Section: Introductionmentioning
confidence: 99%